2020
DOI: 10.1039/d0ra03828h
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of silicates on different length scales exemplified by amorphous mesoporous silica and mesoporous zeolite beta using multiammonium surfactants

Abstract: Reaction gels containing piperidine-based multi-ammonium OSDA yield hierarchical nano-beta zeolite in the presence of aluminum and amorphous mesoporous silica without aluminum, illustrating the highly complex thermodynamic course of zeolite formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The stacked organization of the alkyl chains may have occurred to maximize the van der Waals interactions of the chains [32]. Moreover, it was shown that the morphology of the silica material could be modified as function of the hydrophobization of silica surface with silane precursors.…”
Section: Tem Analysismentioning
confidence: 99%
“…The stacked organization of the alkyl chains may have occurred to maximize the van der Waals interactions of the chains [32]. Moreover, it was shown that the morphology of the silica material could be modified as function of the hydrophobization of silica surface with silane precursors.…”
Section: Tem Analysismentioning
confidence: 99%